1981
DOI: 10.1159/000299611
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Childbirth in Late Pregnancy

Abstract: A consecutive unselected series of 139 pregnant women were personally interviewed during their 31st-33rd week of gestation concerning their feelings at the prospect of the anticipated delivery. A severe fear of childbirth was admitted by 9 women (6%), and another 23 (17%) expressed a more moderate, but still distinct fear of delivery. Fear of physical pain was not found to be a dominant contributing factor, and an augmented service for obstetrical analgesia will, therefore, not suffice to curtail the problem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(97 citation statements)
references
References 0 publications
2
90
2
3
Order By: Relevance
“…Fear of childbirth interfering with the woman's daily functioning is a severe form of tokophobia and referred to as a pathological fear [2]. The prevalence of tokophobia in Western countries is over 20% [2][3][4][5]. An Australian study found that 48% of women reported moderate tokophobia and 26% exhibited strong fear of childbirth [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fear of childbirth interfering with the woman's daily functioning is a severe form of tokophobia and referred to as a pathological fear [2]. The prevalence of tokophobia in Western countries is over 20% [2][3][4][5]. An Australian study found that 48% of women reported moderate tokophobia and 26% exhibited strong fear of childbirth [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fear of childbirth has long been the subject of research interest and clinical attention in the Scandinavian countries [1,2]. More recently it has been explored in other parts of the world with focused research now occurring in Australia [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The most common types of education were motivational interviewing, 17 of 34 responding clinics (50%), and other types of interview methods as basic and advanced counseling skills (15 clinics, 44%). Some clinics had a team member that was educated in CBT (7) or psychotherapy (3). Courses in childbirth fear were mentioned by four clinics.…”
Section: Organization Of the Counseling Teammentioning
confidence: 99%
“…Severe fear of childbirth affects 6-10% of pregnant women [3][4][5], and cesarean section on maternal request is more common among women with childbirth fear [6,7]. In Sweden, women with childbirth fear have been offered counseling by experienced midwives as treatment for their fear in most hospitals since the mid 1990s [8].…”
Section: Introductionmentioning
confidence: 99%